2019
DOI: 10.1097/bot.0000000000001551
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Neck Shortening After Hip Fracture Fixation Is Associated With Inferior Hip Function: Results From the FAITH Trial

Abstract: Objective: To describe the distribution of femoral neck shortening after internal fixation and to determine whether shortening is associated with inferior hip function at 24 months after a hip fracture in patients 50 years of age or older. Design: Retrospective cohort study. Setting: A secondary analysis of data from 81 clinical centers included in the Fixation using Alternative Implants for the Treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 13 publications
2
62
1
Order By: Relevance
“…Standardized radiographic images were obtained pre-operatively, post-operatively, and at 3 and 6 months after surgery, as per standard institutional protocol. Radiological analysis of proximal femur shortening was assessed according to Zhang et al [27] and Felton et al [13] (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Standardized radiographic images were obtained pre-operatively, post-operatively, and at 3 and 6 months after surgery, as per standard institutional protocol. Radiological analysis of proximal femur shortening was assessed according to Zhang et al [27] and Felton et al [13] (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
“…Stable non-displaced (Garden I and II) FNF may be managed with either hip arthroplasty or osteosynthesis [9] and the optimal treatment for such fractures is still subject to debate, depending on several parameters, including the amount of posterior tilt on the axial view [8], [10]. Osteosynthesis is associated with higher complication rates than arthroplasty, such as non-union (20 to 35%) [11], avascular necrosis of the femoral head (23%) [12] fracture impaction and consecutive abductor insufficiency (27%) [13]. This results in revision rates up to 3 times higher than with arthroplasty ranging from 10% to 49% [14,15] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the stability of intertrochanteric fractures involving medial wall injury was not universally affected; medial wall injury accounted for (97.4%) of the patients with posterior-medial fractures, but the radiographic results in patients with type III, IV, and V fractures suggested that the fracture type was relatively stable. HHS function scores indicated a signi cant difference between type I fracture and other fracture classi cations, which also con rmed that neck shortening signi cantly reduced Harris hip scores 18,21,23,5 . Moreover, the postoperative HHS function score of type II fracture with the same posterior-medial involvement was satisfactory.…”
Section: Discussionmentioning
confidence: 65%
“…Femoral neck shortening will be measured from the AP radiograph along the long axis of the femur. This is a frequently used measure after surgical treatment of hip fractures61 62 and is regarded a reliable measure 63…”
Section: Methods and Analysismentioning
confidence: 99%